2019
DOI: 10.1590/2237-6089-2018-0108
|View full text |Cite
|
Sign up to set email alerts
|

Implicit attitudes toward the elderly among health professionals and undergraduate students in the health field: a systematic review

Abstract: Trends in Psychiatry and Psychotherapy Review ArticleResumo Objetivo: Realizar uma revisão sistemática de artigos publicados que avaliam atitudes implícitas em relação ao idoso de profissionais de saúde e estudantes de cursos de graduação da área da saúde. Método: A pesquisa foi realizada nos bancos de dados PsycINFO, PubMed, Web of Science, Scopus e LILACS, buscando artigos relevantes publicados em inglês, português e espanhol. Foram utilizados os seguintes operadores booleanos: implicit attitude AND (elderly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Students realized that older adults in Hong Kong were more knowledgeable than expected. Although students' attitudes towards older adults were not formally accessed in the present study, misconceptions and negative prejudices against older people remained prevalent in health professionals and students of health-related disciplines [34]. When students with negative attitudes towards elderly became health professionals, they were more likely to offer poor patient care [35].…”
Section: Impacts On Studentsmentioning
confidence: 77%
“…Students realized that older adults in Hong Kong were more knowledgeable than expected. Although students' attitudes towards older adults were not formally accessed in the present study, misconceptions and negative prejudices against older people remained prevalent in health professionals and students of health-related disciplines [34]. When students with negative attitudes towards elderly became health professionals, they were more likely to offer poor patient care [35].…”
Section: Impacts On Studentsmentioning
confidence: 77%
“…Allport developed the ‘contact hypothesis’ in 1954, which proposes that contact between members of different groups reduces prejudice (Allport, 1954 as cited in Hughes, 2016). However, simple contact does not seem to be enough as some studies found that professionals with experience (and more frequent contact with older adults) are more negative than students (with less contact) (Gaymard, 2006; Liu, Norman, et al, 2012; Maximiano‐Barreto et al, 2019; Nash et al, 2014). Actually, the ‘beneficial effect of contact’ is present only when certain criteria are fulfilled, such as equal status between protagonists, shared goals and mutual interdependence (Allport, 1954 as cited in Hughes, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, healthcare professionals receive limited education on ageing (Lee et al, 2018; Newell et al, 2004), and this education focuses on diseases and deficits which reduce ageing to a single story of medical decline (Lucchetti et al, 2017) instead of a normal, highly individualised, multidimensional process of growth with maintenance and decline (Rattan, 2014). With the reductive biomedical view, prevalent within the educational environment, students can develop a pessimistic view of ageing and ageist attitudes (Abreu & Caldevilla, 2015; Frost et al, 2016; Maximiano‐Barreto et al, 2019; Schimidt & Paes da Silva, 2012). This could explain the students’ lack of interest in working with older adults (Happell, 2002; Jackson et al, 2017; Kalu et al, 2018; Rathnayake et al, 2016), as well as the ever more negative attitudes towards older patients observed by some studies over the course of their schooling (De Biasio et al, 2015; Kishimoto et al, 2005; Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Another explanation may be the number of female participants in this study. Maximiano-Barreto et al (2019) reported that the majority of studies conducted in developed countries found that males have higher tendency of having negative attitudes toward older adults.…”
Section: Nurses' Attitudes Towards Older Adultsmentioning
confidence: 99%
“…However, according to a systematic review on majority of studies conducted in developed countries, it was found that professionals and undergraduate students in the field of healthcare have negative attitudes towards older adults (Che et al, 2018;Maximiano-Barreto et al, 2019). Rush et al(2017) indicated that hospital nurses' attitudes towards caring for older adults and contributing factors to their attitudes was imperative to inform approaches for improving nurse' attitudes and supporting quality care for older adults.…”
Section: Introductionmentioning
confidence: 99%